Age-Related Changes in Interaural-Level-Difference-Based Across-Frequency Binaural Interference - Goupell, Matthew J. (Frontiers in Aging Neuroscience, 2022)
Low-frequency interaural time differences and high-frequency interaural level differences (ILDs) are used to localize sounds in the horizontal plane. Older listeners appear to be worse at horizontal-plane sound localization to compared younger listeners, but little is understood about age-related changes to across-frequency binaural processing. This study investigated if the frequency dependence of across-frequency ILD processing is altered for older compared to younger listeners, which was done by using an across-frequency binaural interference task (when the interaural difference sensitivity for a target sound is decreased by a spectrally remote interfering sound with zero interaural differences). It was hypothesized that as listeners experience advancing age and age-related high-frequency hearing loss (i.e., presbycusis), they will demonstrate worse binaural performance and experience more across-channel binaural interference (because of age-related temporal processing deficits), and will increasingly be affected by interferers at lower frequencies (because of age-related hearing loss) when compared to younger listeners. There were 11 older (>65 yrs) and 20 younger (<30 yrs) listeners with normal to near-normal audiometric thresholds up to 2 kHz. They were tested using a left-right ILD lateralization discrimination task. Single-tone ILD discrimination thresholds and across-frequency binaural interference were measured at 0.5, 1, 2, 4, and 8 kHz. ILD thresholds and interference was about twice as large for older compared to younger listeners. Interferers ≤1 kHz produced 2–3 times as much across-frequency binaural interference for older compared to younger listeners. Hearing thresholds were significant predictors of single-tone ILD thresholds; in addition, both target and interferer hearing thresholds were significant predictors of binaural interference. The results suggest a reweighting of binaural information that occurs with advancing age and age-related high-frequency hearing loss. This evidence of plasticity may help explain some of the age-related changes in spatial-hearing abilities.